Medical egg freezing: How cost and lack of insurance cover impact women and their families. (April 2018) - Inhorn, Marcia C.; Birenbaum-Carmeli, Daphna; Westphal, Lynn M.; Doyle, Joseph; Gleicher, Norbert; Meirow, Dror; Raanani, Hila; Dirnfeld, Martha; Patrizio, Pasquale
Abstract: Medical egg freezing (MEF) is being recommended increasingly for women at risk of losing their reproductive ability due to cancer chemotherapy or other fertility-threatening medical conditions. This first, binational, ethnographic study of women who had undergone MEF sought to explore women's experiences under two different funding systems: (i) the USA, where the cost of MEF is rarely covered by private or state health insurance; and (ii) Israel, where the cost of MEF is covered by national health insurance. Women were recruited from four American and two Israeli in-vitro fertilization clinics where MEF is offered. In-depth, semi-structured interviews were conducted with 45 women (33 Americans, 12 Israelis) who had completed at least one cycle of MEF. All of the Israeli women had cancer diagnoses, but were not faced with the additional burden of funding an MEF cycle. In marked contrast, the American women – 23 with cancer diagnoses and 10 with other fertility-threatening medical conditions – struggled, along with their families, to 'piece together' MEF funding, which added significant financial pressure to an already stressful situation. Given the high priority that both American and Israeli women in this study placed on survival and future motherhood, it is suggested that insurance funding for MEF should be mandated in the USA, as it is in Israel. This article concludes by describing new state legislative efforts in this regard.